Asymmetric figure-of-eight single-layer suture technique for intestinal anastomosis: A preliminary study - Liu, Mingzhu; Zhang, Mingxiang; Ren, Xiang; Liu, Chen; Yu, Huaijing; Xu, Xiao-Liang; Ding, Guo-Jian; Fu, Tingliang; Geng, Lei; Cheng, Fengchun (Frontiers in Surgery, 2023)
Background: Anastomotic leakage is a life-threatening complication. Improvement of the anastomosis technique is needed, especially in patients with inflamed edematous intestine. The aim of our study is to evaluate the safety and efficacy of an asymmetric figure-of-eight single-layer suture technique for intestinal anastomosis in pediatric patients. Methods: Twenty-three patients underwent intestinal anastomosis at Department of Pediatric Surgery of Binzhou Medical University Hospital. Demographic characteristics, laboratory parameters, anastomosis time, duration of nasogastric tube placement, day of first postoperative bowel movement, complications, and length of hospital stay were statistically analyzed. Follow-up was conducted in a period of three to six months after discharge. Results: Patients were divided into two groups: single-layer asymmetric figure-of-eight suture technique (group 1) and the tradition suture technique (group 2). BMI in group 1 was lower than group 2 (14.43±3.23 vs 19.38±6.74, P=0.036). Mean intestine anastomosis time in group 1 (18.83±0.83 min) was less than that in group 2 (22.70±4.11 min, P=0.005). Patients in group 1 had earlier first postoperative bowel movement (2.17±0.72 vs 2.80±0.42, P=0.023). The duration of nasogastric tube placement in group 1 was shorter than that in group 2 (4.12±1.42 vs 5.60±1.57, P=0.043). There was no significant difference in laboratory variables, complication occurrence, and length of hospital stay between the two groups. Conclusion: The asymmetric figure-of-eight single-layer suture technique for intestinal anastomosis was feasible and effective. More studies are needed to compare the novel technique with the traditional single-layer suture.